EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBASIS PENDEKATAN TEACHING AT THE RIGHT LEVEL TERHADAP MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD - Vanistya Tifani, Agsneta; Winanto, Adi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics is an essential subject in education because it provides the foundation for developing reasoning, logical thinking, creativity, and problem-solving skills. However, mathematics learning in elementary schools still faces challenges, including students' low learning motivation, the perception that mathematics is difficult and uninteresting, and the dominance of conventional teaching methods. Therefore, instructional innovation through the Problem Based Learning (PBL) model based on the Teaching at the Right Level (TaRL) approach is needed. This study aimed to determine the differences in fourth-grade students' mathematics learning motivation and learning outcomes before and after the implementation of the TaRL-based PBL model, as well as the differences between the TaRL-based PBL model and the conventional learning model. This study employed a quantitative approach using a quasi-experimental pretest-posttest control group design. The sample consisted of 46 fourth-grade students. Data were collected through a learning motivation questionnaire, mathematics achievement tests, and observations, and analyzed using the Paired Sample t-Test and MANOVA. The results showed significant differences in learning motivation (p < 0.001) and mathematics learning outcomes (p < 0.05) before and after the implementation of the TaRL-based PBL model. MANOVA also indicated significant differences between the TaRL-based PBL model and the conventional learning model (Wilks' Lambda = 0.034; p < 0.05), supported by the Tests of Between-Subjects Effects for learning motivation (F = 855.427; p = 0.000) and learning outcomes (F = 12.195; p = 0.001). Therefore, significant differences were found in students' mathematics learning motivation and learning outcomes before and after the implementation of the TaRL-based PBL model and between the TaRL-based PBL model and the conventional learning model.